An Investigation Of Dust Suppression In The Pittsburgh Seam - D. H. Davis; G. R. Gardner (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1942)
INCREASING realization of the importance of dust control, and the recommendations of various agencies, have led the mining industry to become actively concerned with this problem. The background and necessity for adequate dust-suppression measures have been discussed in a number of publications, including those of the U. S. Bureau of Mines, and the use of spray water to reduce dust at the face and on roadways has been recommended. The problem resolves itself into obtaining adequate dust reduction at a reasonable cost. Inasmuch as the term "adequate dust suppression" has never been clearly defined, nor have permissible limits of dustiness (in terms of dust count) been established, it is apparent that any method selected may be required to meet additional demands. Until the industry has been given some indication of permissible limits of dustiness, no permanent solution is possible. Progress will be somewhat handicapped until such information is available. In addition, dust reduction must be obtained without the addition of any excessive moisture to the coal, since consideration must often be given to: I. Quality standards, particularly reduction in heat value. 2. Handling characteristics, particularly in regard to unloading from railroad cars and bins. 3. Application of dry methods of coal cleaning. 4. Necessity for fine screening within specified limits of oversize and undersize. Little detailed information is available as to the advantages and disadvantages of the several methods of water distribution, the location and protection of sprays, operating data on pressure, quantity of water, and so forth, and results obtained. In 1940 an investigation was undertaken to determine and evaluate the principal factors involved. This paper constitutes a progress report on this work and cannot in any way be regarded as complete on any one of the several phases. CLASSIFICATION OF DUST SOURCES The various sources of underground dust may be classified as primary or secondary. A primary source is one associated with appreciable degradation of size, that is, where the greater part of the actual fines capable of becoming air-borne dust are produced. A secondary source may be considered as one in which the greater part of the fines have been produced at some previous operation and are in such condition that they can be dispersed as air-borne dust. These conceptions appear to be of practical significance, as experience indicates that when dust is controlled at the primary sources the importance of secondary sources is minimized. For these reasons, investigations to date have been concerned principally with the primary sources of dust, and this paper is concerned particularly with one of these-namely, undercutting. In accord with the foregoing definitions, the sources to which the following opera-